The disinformation in virtual communities: a systematic literature review - Azwar, Azwar; Sarwoprasodjo, Sarwititi; Soetarto , Endriatmo; Lubis, Djuara (Technium Social Sciences Journal, 2023)
This article discusses disinformation in virtual communities. Freedom of speech and freedom of expression are conditions for creating a democratic society. This form of freedom of speech and expression is the creation of a healthy public sphere in people's lives. The real form of a healthy public sphere is that people are free to voice their opinions without being dominated by other parties (structural or non-structural). In addition, people are free to convey ideas and exchange opinions regardless of the existence of power barriers or because of differences in socioeconomic conditions. The public sphere can be created in the realm of reality as well as in virtual space. The intentional, large-scale, and systematic spread of disinformation seriously harms democracy and is a major challenge to democratic societies. Information disorder is not only a problem in Indonesia but has become a problem in many democratic countries in the world. As a problem with humanity, information disorder has been widely studied by various researchers. But the problem is that currently there is no clear concept related to this information chaos. Experts and the public are still confused about defining fake news, hoaxes, or disinformation. As a social problem, a solution to this information disorder is needed. To make a solution to the problem of disinformation, it is necessary to understand the concept of information disturbance clearly. Therefore, this systematic literature review generally aims to ascertain the concept of disinformation, its types, and how to solve disinformation.